2011
DOI: 10.1007/s13318-011-0066-5
|View full text |Cite|
|
Sign up to set email alerts
|

A modified serial blood sampling technique and utility of dried-blood spot technique in estimation of blood concentration: application in mouse pharmacokinetics

Abstract: Pharmacokinetic (PK) studies in mice usually require discrete and parallel blood sampling owing to a restriction on the volume of blood that can be withdrawn. This results in dosing large number of animals and generating composite PK profile. To reduce the number of animals and generate individual animal PK profiles, we developed a serial sampling technique via tail vein bleeding in mice, in which only 20-30 μL blood was withdrawn per time point. Due to the small blood volume, a dried-blood spot (DBS) techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Soon after the administration, the plasma concentration obtained from the lateral tail vein following administration via the lateral tail vein opposite to the blood sampling site was higher than that of the lateral tail vein following administration via the femoral vein (data not shown). This result indicated that blood sampling from the lateral tail vein after administration via the opposite lateral tail vein would be contaminated in spite of different sites being used for administration and sampling, as reported previously . We, therefore, selected the femoral vein as an alternative to the lateral tail vein, which is the conventional dosing route for intravenous administration.…”
Section: Discussionmentioning
confidence: 90%
“…Soon after the administration, the plasma concentration obtained from the lateral tail vein following administration via the lateral tail vein opposite to the blood sampling site was higher than that of the lateral tail vein following administration via the femoral vein (data not shown). This result indicated that blood sampling from the lateral tail vein after administration via the opposite lateral tail vein would be contaminated in spite of different sites being used for administration and sampling, as reported previously . We, therefore, selected the femoral vein as an alternative to the lateral tail vein, which is the conventional dosing route for intravenous administration.…”
Section: Discussionmentioning
confidence: 90%
“…In mice, dihydroartemisinin, the metabolite of artesunate, has a half-life of 25 min, while piperaquine has a significantly longer half-life of 18 days (42,43). Amodiaquine has a half-life of 2.8 h in mice, but it is rapidly metabolized to desethylamodiaquine, which has a half-life in humans of 10 days (44,45). By using this cytocidal murine model of malaria, we determined that extending the interval of 3 doses of artesunate from spanning one asexual cycle to spanning three asexual cycles resulted in a significantly greater reduction in parasite density from the same total amount of drug.…”
Section: Discussionmentioning
confidence: 99%
“…This novel method was minimally invasive, highly robust, and enabled accurate PK determination from small blood volumes (< 20 μL), obviating the need for repeated anesthesia and imaging, for regular tail-vein bleeding, or for the sacrifice of a multitude of mice (22). …”
Section: Discussionmentioning
confidence: 99%
“…A common limitation encountered in many preclinical PK studies is the necessity to sacrifice a multitude of animals at different time points in order to collect both organs and blood samples for nanoparticle and drug analyses (2225). We have previously shown that whole-body NIR-based optical imaging is an inexpensive and easy to use imaging modality that enables noninvasive in vivo biodistribution studies to be conducted in mice (3, 17).…”
Section: Introductionmentioning
confidence: 99%